An Evaluation of Factors Associated with Early Infant HIV Acquisition, Infant Outcomes, and 9-12 Month Infant HIV Seroreversion in the Context of PMTCT Option B+ : Prospective Data from an HIV Exposed Birth Cohort. - Pepper, Michael Sean (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2018.